THE DIFFERENCES OF EXCLUSIVE BREASTFEEDING IN REVIEW OF WORKING AND NOT WORKING PARENTING PATTERNS AT THE HEALTH CENTER OF KABILA BONE - Sunarto Kadir; Irwan Irwan; Dwi Juliani Mertosono (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
ASI eksklusif adalah air susu ibu (ASI) yang diberikan kepada bayi dari lahir sampai berusia enam bulan tanpa makanan tambahan lain. Kebaruan penelitian ini adalah meneliti terkait perbedaan pemberian asi ekslusif di tinjau dari pola asuh ibu bekerja dan tidak bekerja. Tujuan penelitian Untuk mengetahui Perbedaan ASI Ekslusif di Tinjau dari Pola Asuh Ibu Bekerja dan tidak Bekerja di Puskesmas Kabila Bone. Penelitian ini menggunakan metode Penelitian Deskriptif . Sampel dalam penelitian ini yaitu semua populasi ibu yang memiliki balita. Teknik pengambilan sampel pada penelitian adalah Total Sampling. Hasil penelitian menunjukkan pemberian ASI Eksklusif  yaitu 69 (67,0)%, dan yang paling sedikit yaitu 34 (33,0)%. Pola asuh Ibu bekerja dan tidak bekerja yaitu Ibu bekerja 61 (59,2)% dan ibu tidak bekerja 42 (40,8)%. Perbedaan Pola Asuh Ibu Bekerja dan Bukan Bekerja Terhadap Pemberian ASI Eksklusif dari ibu Bekerja memberikan ASI berjumlah 11 (10,7) dan tidak memberikan ASI 50 (48,5), Sedangkan tidak bekerja yang memberikan ASI berjumlah 23 (22,3)% dan tidak memberikan ASI 19 (18,4)%. Simpulan Adanya perbedaan antara pola asuh ibu Bekerja dan ibu tidak bekerja terhadap pemberian ASI Eksklusif.Kata Kunci: ASI Eksklusif; Pola asuh; Ibu bekerja dan tidak bekerja.AbstractExclusive breastfeeding is mother's milk (ASI) given to babies from birth to six months of age without any other additional food. The novelty of this study is to examine the differences in exclusive breastfeeding in terms of the parenting patterns of working and non-working mothers. The purpose of the study was to determine the difference between exclusive breastfeeding in terms of parenting patterns for working and non-working mothers at the Kabila Bone Health Center. This research uses descriptive research method. The sample in this study is all the population of mothers who have toddlers. The sampling technique in this research is Total Sampling. The results showed that exclusive breastfeeding was 69 (67.0%), and the least was 34 (33.0)%. Parenting patterns of working and non-working mothers are working mothers 61 (59.2)% and mothers not working 42 (40.8)%. Differences in Parenting Patterns of Working and Non-Working Mothers on Exclusive Breastfeeding of working mothers giving breast milk amounted to 11 (10.7) and did not give breast milk 50 (48.5), while those who did not work gave breast milk amounted to 23 (22.3)% and not giving breast milk 19 (18.4)%. Conclusion There is a difference between the parenting pattern of working mothers and non-working mothers towards exclusive breastfeeding.